Dynamics and Effectiveness of Regional Own-Source Revenue: A Comparative Study of West Java and Central Java Before and During the COVID-19 Pandemic - Dermawan, Indra Setia; Aulia, Azwani; Saputri, Eka Julianti Efris (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study analyzes the dynamics, composition, and effectiveness of regional own-source revenue in the provincial governments of West Java and Central Java before and during the COVID-19 pandemic. A qualitative descriptive approach with a comparative case study design was employed using secondary data derived from regional government financial statements, regional budget documents, and official government publications for the years 2019 and 2020. The findings indicate that local taxes constitute the primary source of revenue in both provinces, followed by income from separated regional assets, other legitimate revenues, and regional service charges. The COVID-19 pandemic did not alter the fundamental revenue structure but significantly reduced revenue realization, particularly in components closely linked to economic activity. Furthermore, the effectiveness ratio of revenue collection declined during the pandemic, especially in West Java.